Top-quark asymmetry: a new physics overview - Westhoff, Susanne (Arxiv, 2011)
Several recent measurements at the Tevatron experiments point towards an anomalously large forward-backward asymmetry in top-antitop production. This article summarizes the main classes of physics beyond the standard model that can give rise to a large asymmetry. Complementary measurements at the Large Hadron Collider will allow to distinguish between different models and thereby contribute to clarifying the presently puzzling picture.
Gesehen am 10.01.2018